2022
DOI: 10.1016/j.euo.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Using Prostate Imaging-Reporting and Data System (PI-RADS) Scores to Select an Optimal Prostate Biopsy Method: A Secondary Analysis of the Trio Study

Abstract: a on behalf of the Trio Study Group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 40 publications
4
19
0
2
Order By: Relevance
“…In men with prior negative systemic biopsies, an additional systematic biopsy was avoidable in 58%, while missing GG ≥ 2 cancer in 2%. These findings are concordant with the analysis of Ahdoot et al who showed a greater added value for MRTB men with PI-RADS 4-5 lesions and a greater added value of systemic biopsies for men with lower PI-RADS category scores [6]. Their analysis of the TRIO study confirmed that improved GG ≥ 2 detection of combined biopsies was restricted to only men with smaller (PI- RADS 4) or indeterminate (PI-RADS 3) MRI lesions.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…In men with prior negative systemic biopsies, an additional systematic biopsy was avoidable in 58%, while missing GG ≥ 2 cancer in 2%. These findings are concordant with the analysis of Ahdoot et al who showed a greater added value for MRTB men with PI-RADS 4-5 lesions and a greater added value of systemic biopsies for men with lower PI-RADS category scores [6]. Their analysis of the TRIO study confirmed that improved GG ≥ 2 detection of combined biopsies was restricted to only men with smaller (PI- RADS 4) or indeterminate (PI-RADS 3) MRI lesions.…”
supporting
confidence: 86%
“…Their analysis of the TRIO study confirmed that improved GG ≥ 2 detection of combined biopsies was restricted to only men with smaller (PI- RADS 4) or indeterminate (PI-RADS 3) MRI lesions. Not undertaking systemic biopsies in men with PI-RADS 5 category lesions would lead to missing GG ≥ 2 cancers in 1.3% [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified the clinical setting (biopsy naïve, previous negative biopsy, active surveillance), age, prostate volume, MRI-lesion volume and the PI-RADS Score [ 7 , 8 , 9 ] predictive for upgrading to sPC by SB. A recent study proposed patients’ PI-RADS score as a promising tool to select the optimal biopsy strategy [ 10 ]. However, these findings are limited to a cohort who underwent transrectal prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Gecombineerde biopten geven ook een betere inschatting van prostatectomie-uitkomsten, alhoewel dit verschil beperkt is en met name wordt veroorzaakt door Gleason 3+4-tumoren [8]. Bij MRI PI-RADS 5-laesies is de toegevoegde waarde van systematische biopten relatief het kleinst [9].…”
Section: Introductieunclassified